The Bird-Woman of the Lewis and Clark Expedition - Chandler, Katherine, 1865-1930 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Bird-Woman of the Lewis and Clark Expedition" by Katherine Chandler is a historical account written in the early 20th century. This book serves as a supplementary reader designed for first and second-grade students, recounting the journey of the Lewis and Clark Expedition with a focus on Sacajawea, an indigenous woman who played a crucial role in guiding the explorers through uncharted territory. The narrative is based on true events documented in the Lewis and Clark Journals, making it both educational and engaging for young readers. The story follows Sacajawea from her early life with the Snake Indians to her joining the expedition alongside Meriwether Lewis and William Clark. After being taken from her tribe, she marries a French trapper and eventually becomes an essential member of the expedition as they journey across the American wilderness. Sacajawea's knowledge of the land and her ability to communicate with different tribes help the party navigate challenges and establish favorable relations with various Indigenous peoples they encounter. Her contributions range from logistical support to practical survival skills, such as finding food sources and medicine for her fellow travelers. Through her story, readers gain insight into the trials faced by the expedition and the significant impact of Sacajawea, often referred to as the "Bird-Woman," on their successful journey. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Readers (Primary); Sacagawea -- Juvenile literature; Lewis and Clark Expedition (1804-1806) -- Juvenile literature